1986
DOI: 10.1111/j.1399-3054.1986.tb06589.x
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular transpiration and epicuticular lipids of primary leaves of barley (Hordeum vulgare)

Abstract: LarssoD, S. and Svenningsson, M. 1986. Cuticular tran^iratioo and epicuticular lipids of primary leaves of barley (Hordeum vulgare) . Twenty cultivars of barley and 15 eceriferum mutants from one of the cultivars have been analysed for cuticular transpiratioii and epicuticular lipids of their primary leaves. The relative cuticular transpiration rates of the cultivars ranged from 0.61 to 1.98. In spite of this variation in transpiration most of the cultivars had almost the same amount of epicuticular lipids per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…A similar correlation of multiple drying events to wax deposition was originally shown for seedlings from five oat cultivars (Bengtson et al, 1978), although a subsequent study found no significant correlation for two of the cultivars (Svenningsson and Liljenberg, 1986). No relationship was found between epidermal conductance and wax load in barley (Hordeum vulgare) cultivars that were subjected to dehydration stress (Larsson and Svenningsson, 1986). However, transpiration rates were significantly higher and yield significantly lower in bloomless cultivars of sorghum than in isogenic normal bloom cultivars of sorghum (Chatterton et al, 1975).…”
Section: Discussionmentioning
confidence: 57%
“…A similar correlation of multiple drying events to wax deposition was originally shown for seedlings from five oat cultivars (Bengtson et al, 1978), although a subsequent study found no significant correlation for two of the cultivars (Svenningsson and Liljenberg, 1986). No relationship was found between epidermal conductance and wax load in barley (Hordeum vulgare) cultivars that were subjected to dehydration stress (Larsson and Svenningsson, 1986). However, transpiration rates were significantly higher and yield significantly lower in bloomless cultivars of sorghum than in isogenic normal bloom cultivars of sorghum (Chatterton et al, 1975).…”
Section: Discussionmentioning
confidence: 57%
“…Other authors have also reported a lack of such a relationship in oats (Svenningsson and Liljenberg 1986), barley (Larsson and Svenningsson 1986) and wheat (Araus et al 1991;Haley et al 1993). This lack of a correlation may be due to the barrier to the diffusion of water across the cuticle depending on the structure and distribution of the epicuticular waxes and the type of intracuticular waxes present (Larsson and Svenningsson 1986). In oats it has been reported that changes in the intracuticular lipids occur in parallel with a reduction in the residual transpiration as a response to water stress (Svenningsson and Liljenberg 1986).…”
Section: Discussionmentioning
confidence: 89%
“…Although the epicuticular wax of all plant species consist of alkanes, primary and secondary alcohols, wax monoesters, aldehydes and free fatty acids, the quantitative distribution differs according to species. In barley, primary alcohols are the main epicuticular wax component (Larsson and Svenningsson 1986;Steinmüller and Tevini 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, wax coverage increased upon terminal drought stress treatment and this was associated with drought tolerance. On the other hand, the significance of high epicuticular wax load in residual transpiration and drought tolerance has been disputed by others (Larson and Svenningson, 1986;Merah et al, 2000). Glaucousness appeared to confer an advantage to near isogenic wheat lines under rain-fed conditions, rather than in very dry environments (Johnson et al, 1983).…”
Section: Discussionmentioning
confidence: 99%